The effects of subsidized housing on the property values of neighbourhoods within its vicinity - Malgas, Shannon M (School of Economics, 2018)
Over time neighbourhoods have shown opposition to Government subsidized housing programmes being developed within their neighbourhoods. This is due to the perceived negative impacts that these housing developments have on the neighbourhood. Opposition has grown since implementation of the Housing Code of 2009. The Code aims to integrate low income households into more affluent areas, in order to provide these households with greater access to economic and social opportunities, which they were previously denied having been placed on the urban periphery. Opponents to subsidized housing developments have nevertheless expressed concerns with a possible decline in property values. These concerns are however based on perception, rather than factual evidence to this effect. There is a paucity of studies on the topic within the South African context. While there are a number of studies on the topic within other countries, the results cannot be generalized due to the difference in demographics, housing subsidy programmes and structure of the City of Cape Town. An analysis of the impact within the City of Cape Town context may thus be beneficial. This paper analysed the impacts of Residential Development Programme (RDP) housing and Social Housing (rental) projects, as these are the subsidized housing developments that have received the most opposition. The paper has thus used a Difference-in-Difference Hedonic Pricing Model analysis to determine the neighbourhood impacts of subsidized housing on the property values of surrounding neighbourhoods. RDP housing was estimated to have a negative effect on proximate property values, while Social Housing was estimated to have no effect. It is recommended that future developments are aesthetically appealing, have landscaping, are well maintained and are well integrated with the surrounding community. These efforts should also be well communicated to the host communities during the public participation events. Further analysis is required to determine the cause of the negative effects of the RDP development to ensure that these are mitigated in future RDP projects. These may allow the State to provide the much-needed housing opportunities, with limited opposition from the host communities.